Association between multimorbidity and levels of quality of life: A population-based study in the north of Peru - Guerra-Bartra, Oscar André (2025)
Objective: To assess whether there is an association between the number of chronic conditions (multimorbidity) and quality of life, and if this relationship varies by social support. Materials and Methods: Secondary data analysis of a population-based survey enrolling randomly selected individuals between 30 and 69 years, in northern Peru. The dependent variable was quality of life, assessed using the EQ-VAS, part of the EuroQol, whereas the exposure variable was the number of chronic conditions (multimorbidity: ≥2 chronic conditions). Linear regression models with robust variance were built to assess the association of interest, reporting coefficients and 95% confidence intervals (95% CI). Results: A sample of 1607 individuals, mean age of 48.2 (±10.6) years, and 49.7% men, was analyzed. Multimorbidity was present in 39.5% (95% CI: 37.1%-41.9%), whereas the mean quality of life was 72.4 (±16.6). In multivariable model, those with multimorbidity had 6.54 (95% CI: 4.84-8.24) fewer points than those who did not have multimorbidity. This score decreased with an increasing number of chronic conditions: 2.07, 5.73, and 11.5 fewer points for those with 1, 2, and 3+ chronic conditions. There was no evidence that social support was an effect modifier of such association. Conclusions: There is an inverse association between the number of chronic conditions (multimorbidity) and quality of life. Social support was not an effect modifier of this association. Our results suggest the use of appropriate strategies for the management of patients with multiple chronic conditions.